Hubungan Antara Asupan Zat Gizi Makro saat Sarapan dengan Konsentrasi Siswa SMAN 1 Grogol, Kediri - Alya Rifqi Ghifari; Cleonara Yanuar Dini (Lembaga Pengembangan Kinerja Dosen, 2025)
Breakfast is important for school students, especially teenagers because schools are full of activities that require a large amount of energy that can impact concentration. This study aims to determine the relationship between macronutrient intake during breakfast and the concentration of students of SMA Negeri 1 Grogol, Kediri. The design of the study is descriptive analytics with a cross-sectional research design including a total of 88 students. The sampling technique is simple random sampling. Breakfast data collected using food recall and concentration levels used Grid Concentration Test sheets. The data analysis technique used Somers’d. The result showed there is a significant relationship between carbohydrate (p = 0,017; r = 0,219) and protein intake (p = 0,008; r = 0,266) consumed at breakfast and student concentration, the relationship between the two variables was quite weak, but there was no significant relationship between intake of fat consumed at breakfast and student concentration (p = 0,220; r = 0,112). The conclusion of this study is that carbohydrate and protein intake consumed at breakfast is associated with student concentration.